Spatially resolved analysis of sequential, single track laser re-nitriding in titanium - Inga K. Goetz; Marcus Hans; Ulf Jansson; Björgvin Hjörvarsson; Jochen M. Schneider (Next Materials, 2024)
Applying nitriding in laser powder bed fusion additive manufacturing at custom build positions requires knowledge of the spatially and temporally resolved nitriding behaviour. Here we take steps toward this goal by sequential analysis of spatially resolved structural, chemical, and mechanical information throughout the melt pool, which is not available in previous studies. Single laser nitriding tracks are produced in a laser powder bed fusion system. By re-nitriding the initially nitrided track two more times, the effect of multiple sequential nitriding steps on the spatially resolved evolution of composition, structure, morphology and mechanical properties is captured. Characterisation is carried out by X-ray diffraction on the top of the laser tracks as well as laser optical microscopy, energy dispersive X-ray spectroscopy, electron backscatter diffraction, and nanoindentation on the melt pool cross sections. Nitrogen incorporation and TiN formation is observed at > 200 μm melt pool depth and it is evident that multiple sequential laser passes increase the TiN fraction. The nitrogen incorporation results in a gradient of the mechanical properties with enhanced hardness and elastic modulus depending on the local nitride fraction. A maximum local hardness of ∼ 20 GPa is observed and a melt pool hardness of 7.3 ± 1.7, 9.3 ± 3.5, and 10.3 ± 5.2 GPa is attained for one, two and three melts. Compared to the Ti substrate with a hardness of ∼ 2.5 GPa, substantial local modifications are obtained.